Education for All: The Evaluation of Inclusive Education Program in Elementary School in Jakarta, Indonesia - BAHRUDIN,; JAYA, INDRA; ABIDIN, IBRAHIM; HARTATI, SOFIA; RUGAIYAH5, RUGAIYAH (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identified the implementation of inclusive education programs in elementary schools in Jakarta, Indonesia. The effectiveness of inclusive education programs can be known through an internal and external aspects of evaluation. So that it can be known obstacles, benefits and impacts of the program as well as a variety of important information that is useful for the implementation of future programs. This research uses an exploratory sequential mixed-method approach through two phases, qualitative and quantitative. This research collaborated with two elementary schools in Jakarta, 52 elementary school students, 160 parents of elementary school students, and 5 elementary school teachers. General students have a positive attitude towards students with special needs. Based on teacher input shows that a lot of teachers meet administrative requirements is graduated from Bachelor Degree in education. Several of school already has a special assistant teacher even though not yet present in one week, but teachers have developed individual curriculum with the needs and abilities of students.